Penanggulangan Tindak Pidana Terhadap Penyalahgunaan Narkotika Pada Anak - Perdana, Mulki Aja; Fajar, M. (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This study was conducted with the aim of finding out how the crime of drug abuse in minors. Children as the young generation who are the successors of the nation's ideals and contribute to national development. It is estimated that 100% of the population of Indonesia are victims of drug abuse. Abusers are people who use narcotics without rights or against the law. Ensuring the availability of narcotics for the benefit of health services and/or the return of knowledge, preventing drug abuse; and eradicating illicit drug trafficking. In addition, prevention efforts need to be carried out by parents, themselves, the government, and the local environment. The basis for the creation of Law No. 35/2009 concerning Narcotics is to realize a just and prosperous society by increasing the level of human resources, a legal approach and regulating drug trafficking.